What do hotel guests really want? An analysis of online reviews using text mining - Ristova Maglovska, Cvetanka (Hotel and Tourism Management, 2020)
Hotels offer a range of attribute-based services perceived to be wanted and gladly used by guests while staying at the hotel. That is, hotels at least think they have recognized the attributes of importance to their guests. Whether there is a desire for high-quality Wi-Fi, touchscreen technology, RFID or even tablet-controlled hotel room to satisfy the digital-savvy guests or small fridge, microwave and tea for families, hotels today find themselves into a position where online reviews represent one of the most valuable tools for getting insights into the factors that determine guests’ experiences. By scraping the online reviews of 21 five-star hotels in North Macedonia on Booking.com, this paper investigates the attributes that are affecting guests’ experience by analyzing the sets of online reviews using text mining. Research findings offer a more consistent understanding of the guest experience expressed in online reviews in terms of determining which amenities enhance guest satisfaction. The paper also illustrates how the methodological approach of text mining enables the use and visual interpretation of the data, and thus contributes to the studies in the field of hotel management.